The perfectionist's handbook : take risks, invite criticism, and make the most of your mistakes - Szymanski, Jeff (Wiley, 2011)
"Go for the gold. Achieve. Stand out. It's the American way to aim for perfection and excel in business, school, sports, and life. We're all trying to do more in less time and feeling overwhelmed as a result. But too many people in business are ineffecient, self-sabotaging perfectionists. If you spend three hours editing an annual report to get it 90% perfect, and then spend another two hours to get it 93% perfect, and another hour for 95% perfect, the incremental improvement is negligible. Think of the time and effort you can conserve and redistribute to other tasks. Unlike other negative advice given, to give up your perfectionism, The Perfectionist's Handbook challenges this mindset which makes it unique. Jeff Szymanski tells readers they got the right idea, but you're taking the wrong paths to achieve the outcome you want. The Perfectionist's Handbook teaches the art of being an Adaptive Perfectionist, someone who stands out and gets bigger playoffs: greater productivity with less effort, more energy, and balance in your work and life. Jeff's strategies to function more effectively and better reach your goals include: Analyze Your Effort Focus on Your Top 10 List Lose the Parachute Embrace Failure Shift and Delegate Secretly Observe Others Refuel and Refresh Invite Criticism "--Provided by publisher